Comparative study of the thermal and power performances of a semi-transparent photovoltaic façade under different ventilation modes. (15th January 2015) - Peng, Jinqing; Lu, Lin; Yang, Hongxing; Ma, Tao
Highlights: A ventilated photovoltaic double-skin façade (PV-DSF) using semi-transparent a-Si was reported. The impact of different ventilation modes on the power performance of PV-DSF was studied experimentally. The SHGCs and U -values of PV-DSFs under different ventilation modes were calculated and compared. An optimum operating strategy was proposed for this PV-DSF to achieve the best energy efficiency. Abstract: This paper studied the thermal and power performances of a ventilated photovoltaic façade under different ventilation modes, and appropriate operation strategies for different weather conditions were proposed accordingly to maximize its energy conversion efficiency. This ventilated PV double-skin façade (PV-DSF) consists of an outside layer of semi-transparent amorphous silicon (a-Si) PV laminate, an inward-openable window and a 400 mm airflow cavity. Before installation, the electrical characteristics under standard testing conditions (STC) and the temperature coefficients of the semi-transparent PV module were tested and determined in the laboratory. Field measurements were carried out to investigate the impact of different ventilation modes, namely, ventilated, buoyancy-driven ventilated and non-ventilated, on the thermal and power performances of this PV-DSF. The results show that the ventilated PV-DSF provides the lowest average solar heat gain coefficient (SHGC) and the non-ventilated PV-DSF provides the best thermal insulation performance. In terms of power performance, the energy output of the ventilated PV-DSF is greater than those of the buoyancy-driven ventilated and non-ventilated PV-DSFs by 1.9% and 3%, respectively, due to its much lower operating temperature. Based on the experimental results, a conclusion was drawn that the ventilation design can not only reduce the heat gain of PV-DSF but also improve the energy conversion efficiency of PV modules by bringing down their operating temperature. In addition, an optimum operation strategy is recommended for this kind of PV-DSF to maximize its overall energy efficiency under different weather conditions.